Defect-engineering of Pt/Bi4NbO8Br heterostructures for synergetic promotional photocatalytic removal of versatile organic contaminants. Issue 8 (29th January 2021) - Shi, Liang; Wu, Xilu; Xu, Chonglei; Bai, Qiang; Nie, Zhen; Ji, Chengcheng; Zhang, Yelong; Yin, Zhengmao; Zhang, Shuai; Qu, Xiaofei; Du, Fanglin
Abstract : Defective Pt/Bi4 NbO8 Br composites were fabricated via a facile in situ chemical reduction method. The synergistic effect of Pt and oxygen vacancies endows the hybrid photocatalysts with enhanced efficiency for versatile organic pollutant removal. Abstract : A strategy to improve its photocatalytic performance is still a challenge for the novel Sillen–Aurivillius perovskite type Bi4 NbO8 Br. Herein, novel Pt modified Bi4 NbO8 Br composites (Pt/BNB) with sufficient oxygen vacancies were successfully fabricated via a facile in situ chemical reduction method. For one thing, the deposition of Pt nanoparticles brings about a Mott–Schottky effect at the interface to accept photo-induced electrons, leading to an efficient charge separation. For another thing, the electronic metal–support interaction of Pt and Bi4 NbO8 Br decreases the formation energy of oxygen defects, which could serve as active sites for O2 activation. On account of the synergetic effect of Pt and oxygen vacancies, the dominant active species-photogenerated holes are accumulated on the surface of the photocatalysts, while the additional superoxide radicals are also involved. Hence, Pt/BNB performed with excellent photocatalytic activities in the degradation of wastewater contaminants, and the kinetic rate was 4.64, 10.21, 5.53, 9.80, 1.71 and 4.05 times, respectively, those of pristine Bi4 NbO8 Br towards methyl orange, rhodamine B, 2, 4-dichlorophenol, p -nitrophenol, ciprofloxacin and tetracycline hydrochloride.